Grassroots Dissemination of Adult Education Research in Africa: Results of Recent Experience in Benin and Botswana - Peter Easton; Christine Capacci (Adult Education Research Conference, 1999)
Adult education research is a very small industry in Africa, one whose products are underutilized in practice. This paper describes an initiative designed to promote "grassroots dissemination", in which African researchers and NGOs help target groups to work through relevant research results and compare them with their own experience.